Efficacy of the transcutaneous electrostimulation in treatment dysfunctions of the TMJ associated with occlusion distortions - Zhanna Khachatryan; Tsovinar Hambartsoumian; Lyudmila Tatintsyan; Seda Burnazyan; Gagik Hakobyan (BMC, 2023)
Abstract Background The study evaluation of the effectiveness the method of electrostimulation in treatment TMJ associated with occlusion disorders with the use of a patches by the company "Aganyan''. Methods The study included 54 patients with temporomandibular dysfunction syndrome who had previously undergone endodontic dental treatment. In patients temporomandibular disorders (TMD) determined on the basis of Diagnostic criteria for temporomandibular disorders(DC/TMD).All patients had occlusion disorders due to errors after dental filling restoration. To diagnose the TMJ, a CT scan was used. The complex therapy also included therapy and with the use of a patches by the company "Aganyan''. The wearable patch includes a flexible substrate, a binder an adhesive layer, with an electrode foil attached to it. Patients applied one patch behind each TMJ. The patches were applied for eight hours every third day for three months. All the patients were given full-fledged endodontic treatment and restoration of the crown part, taking into account anatomical features. Results The dynamics of the complex treatment of patients diagnosed with TMJ dysfunction syndrome showed that after treatment, the clinical symptoms gradually decreased and disappeared at the end of treatment. CT scan a year after treatment showed a normal ratio of TMJ elements. Сomplex treatment was effective in 87% of patients, after 3-5 months gradually decreased pain, noise in the joints, restriction of opening and closing of the mouth disappeared. Patients recovered their chewing functions, psycho-emotional state. Conclusion The results of the studies revealed a positive effects for the complex treatment dysfunctions syndrome TMJ the using the patches by the company "Aganyan" through electrical stimulation with low intensity.